Comparison of the different techniques to remove fractured endodontic instruments from root canal systems - (:unkn) unknown (My University, 2009)
OBJECTIVES: To evaluate the success of certain methods that can be used in the removal of separated instruments from different levels in curved and straight canals. METHODS: Instrument removal attempts were undertaken on 63 straight and 30 curved canals containing a pre-fractured instrument using the ultrasonics under the visualization of an operating microscope or conventional methods. In straight canals, a Masseran Kit was additionally used to these techniques. The success of instrument removal in relation to the techniques used and the location of the fragments in the root canal were evaluated. Successful treatment was defined by the removal or complete by passing of the fragments. RESULTS: The overall success rate was found 93.3% with ultrasonics and 66.6% when only conventional methods were used in curved canals. In straight canals, also the success rate was the highest with ultrasonics (95.2%). This was followed by conventional method (80.9%) and the least by Masserann Kit (47.6%). When the success rate was investigated according to the location of the broken instruments, the lowest rate was found in the apical third of root canal. CONCLUSIONS: Location of the fragment and the shape of the root canal influence the success of fractured instrument management. Ultrasonics under the visualization of an operating microscope was found to be an effective removal method.
Keywords: Ultrasonics; Fractured instrument; Instrument removal; Masserann Kit; Operating microscope